Examining Patterns of the Quality and Satisfaction of Marriage in Polygamous Families - Abd Razak, Muhammad Ajib (International Journal of Psychosocial Rehabilitation, 2020)
Previous studies on polygamy tend to focus on how polygamous marriages contribute more to conflicts and negative family dysfunction compared to monogamous marriages. This study aims to gain more understanding of polygamous marriages by investigating the quality and satisfaction of family members who practiced polygamy in Malaysia. A total of six families were interviewed. This involved 21 respondents consisting of six husbands, five first wives, five second wives, one third and fourth wife, as well as three children, all of whom were interviewed based on predetermined inclusion criteria using purposive sampling. Qualitative study taking phenomenological approach was used in this study. In-depth face-to-face interviews were conducted based on the interview questions that developed earlier. Interviews were transcribed and analyzed using thematic analysis and six themes emerged as follows: greater appreciation and understanding, applying knowledge and conducting activities in the household, positive interactions between wives and co-wives, respect for the opinions and views of wives and co-wives, patience in learning to understand the characters of husband/co-wives and, from the children's perspectives, a desire for their fathers to give them advice and guidance, and to help and resolve family problems while managing their family well. In conclusion, polygamous marriage can produce a form of marriage quality and satisfaction based on the themes emerged from the interviews with the respondents as they seek to maintain the psychological well-being of family members. These findings also serve as important information in developing instruments and intervention modules, and for suggesting prospective dimensions and indicators of well-being that can promote the positive development of polygamous families.